Design, physico-chemical and pre-clinical evaluation of a homo-bivalent 99mTc-(BTZ)2DTPA radioligand for targeting dimeric 5-HT1A/5-HT7 receptors. (16th August 2018) - Jha, Preeti; Chaturvedi, Shubhra; Kaul, Ankur; Pant, Pradeep; Anju,; Pal, Sunil; Jain, Nidhi; Mishra, Anil K.
Abstract : A 99m Tc-labelled bis-benzothiazolone-DTPA radio-complex as a SPECT neuroimaging agent. Abstract : A mixed affinity dimeric radioligand 99m Tc-(BTZ)2 DTPA was designed using a "bivalent ligand approach" and evaluated as an SPECT imaging agent for targeting 5-HT1A /5-HT7 dimeric receptors in the central nervous system. In silico studies reflected high affinity for dimeric 5-HT1A /5-HT7 receptors. Following multi-step synthesis, the ligand was obtained in 87.5% yield. Detailed physico-chemical analysis included p K a evaluation and optimization of radiolabeling parameters (>98% radiolabeling efficiency). The in vitro serum-stability test of the 99m Tc-complex showed ≤8.7% dissociation and appreciable stability when challenged with excess cysteine (≤4.4% dissociation). Cyto-compatibility (4.8–0.6% cell death at 100 μM to 1 pM) and haemo-compatibility (1.05% erythrocyte destruction) suggested optimum biocompatibility. Blood kinetics revealed biphasic clearance. The brain/blood ratio of 0.66 assured the CNS penetration ability and BBB permeability of the developed radioligand. Bio-distribution and in vivo SPECT imaging revealed a maximum brain uptake of 2.08 ± 0.08% ID per g at 10 min p.i. followed by major activity accumulation in 5-HT1A /5-HT7 receptor-rich regions viz., the hippocampus (41.83% ID per g) and the cortex (23.56% ID per g) of mouse brains ascertaining selective targeting of 99m Tc-(BTZ)2 DTPA. The radiotracer was excreted majorly through the renal route. These preclinical studies reveal that the 99m Tc-(BTZ)2 DTPA radiotracer shows promise as an effective diagnostic agent for neurological disorders.